Oxygen‐Induced 1D to 2D Transformation of On‐Surface Organometallic Structures. Issue 35 (6th August 2020) - Ji, Penghui; Galeotti, Gianluca; De Marchi, Fabrizio; Cui, Daling; Sun, Kewei; Zhang, Haiming; Contini, Giorgio; Ebrahimi, Maryam; MacLean, Oliver; Rosei, Federico; Chi, Lifeng
Abstract: While surface‐confined Ullmann‐type coupling has been widely investigated for its potential to produce π‐conjugated polymers with unique properties, the pathway of this reaction in the presence of adsorbed oxygen has yet to be explored. Here, the effect of oxygen adsorption between different steps of the polymerization reaction is studied, revealing an unexpected transformation of the 1D organometallic (OM) chains to 2D OM networks by annealing, rather than the 1D polymer obtained on pristine surfaces. Characterization by scanning tunneling microscopy and X‐ray photoelectron spectroscopy indicates that the networks consist of OM segments stabilized by chemisorbed oxygen at the vertices of the segments, as supported by density functional theory calculations. Hexagonal 2D OM networks with different sizes on Cu(111) can be created using precursors with different length, either 4, 4″‐dibromo‐ p ‐terphenyl or 1, 4‐dibromobenzene (dBB), and square networks are obtained from dBB on Cu(100). The control over size and symmetry illustrates a versatile surface patterning technique, with potential applications in confined reactions and host–guest chemistry. Abstract : On‐surface Ullmann‐type coupling with linear precursors typically forms a 1D organometallic intermediate en route to a 1D polymer. Introducing oxygen leads to the unexpected transformation of this intermediate to highly ordered 2D organometallic networks. The network size and shape can be rationally controlled by changing the precursor length and substrate symmetry, making them promising templates for host–guest systems.